Optimization of School Security Patrol Development by Traffic Security and Safety Unit of Semarang Big City Police Station in Order to Improve Senior High School Student Traffic Order - Setiyawan, Alfian Budi (Indonesian Journal of Police Studies, 2024)
This research is motivated by the high number of violations and accidents in the city of Semarang committed by teenagers ( age 10-18 years ) who are in high school. besides that there is an organization that exists in these circles , in their school namely the school security patrol which is lacking get coaching from the Camsel Unit . So the problem of this research is that the supervision of school security patrols at the senior high school level by the Kamsel unit is not optimal traffic Polrestabes Semarang . The aim of this research is To find out the efforts to foster patrol i school security at the senior high school level carried out by the Kamsel unit traffic Polrestabes Semarang and Analyzing patterns coaching patrol school security used by the Kamsel unit traffic Polrestabes semarang to build students and students patrol high school level school safety top . This study uses qualitative methods with data collection techniques, namely interviews, observation, and document study. Meanwhile, the validity and reliability of the research data used a data triangulation technique using data analysis in the form of data reduction, data presentation, and drawing conclusions. The concepts used are the concept of optimization, school security patrols, and the concept of security and safety . Meanwhile, the theory used is management theory ( POAC and 6M ) and SWOT theory. Based on research results according to the Chief of Police's Juklak No.Pol : Juklak/05/V/2003 concerning Community Education on Traffic, school safety patrols are a forum for student participation in the field of traffic, especially arranging crossings on public roads in their respective school environments. Guidance on school security patrols at the senior high school level has not been implemented properly at SMAN 5 Semarang. So far, the guidance provided by the Kamsel unit has stopped due to the pandemic and has shifted its focus to coaching among elementary school children ( age 6-12 years ) . This even becomes ineffective in tackling the high number of juvenile violations and accidents. According to the results of the research, the authors provide a solution to the problem in the form of implementing school safety patrol coaching at the high school level, especially SMA Negeri 5 Semarang, which is good and utilizes existing technology to optimize it.